2018
DOI: 10.1007/s00431-018-3247-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of clinical outcome of children with sepsis outside the intensive care unit

Abstract: In 2016, in order to identify adult patients with sepsis who are likely to have poor outcomes, the Third International Consensus Definitions Task Force introduced a new bedside index, called the quick Sepsis-related Organ Failure Assessment (qSOFA) score. However, these new criteria have not been validated in the pediatric population. In this study, we sought to assess the qSOFA score for children with sepsis, who are being treated outside the pediatric intensive care units. The qSOFA criteria were revised and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
4
1
1
Order By: Relevance
“…Overall, the LqSOFA demonstrates superior discriminative ability than that reported with the qSOFA in the pediatric population, both in the current study and compared with previous research. 6,9,30 In the current study, the LqSOFA revealed the greatest positive predictive value of all 4 scoring systems, although this was only 34%. The low values for positive predictive value seen across all scoring systems likely reflect the low prevalence of sepsis within the ED population and highlight the difficulty in identifying such cases.…”
Section: Figurecontrasting
confidence: 55%
“…Overall, the LqSOFA demonstrates superior discriminative ability than that reported with the qSOFA in the pediatric population, both in the current study and compared with previous research. 6,9,30 In the current study, the LqSOFA revealed the greatest positive predictive value of all 4 scoring systems, although this was only 34%. The low values for positive predictive value seen across all scoring systems likely reflect the low prevalence of sepsis within the ED population and highlight the difficulty in identifying such cases.…”
Section: Figurecontrasting
confidence: 55%
“…Se cuenta con estudios que evaluaron si la disfunción orgánica podría ser también el centro de la definición en sepsis pediátrica (Tabla 2) [57][58][59][60][61][62][63] .…”
Section: Sepsis-3 Se Extiende a La Pediatríaunclassified
“…Six studies 13,24,25 were designed to evaluate the value of the age-adjusted qSOFA in predicting mortality. Four studies 24,35 evaluated the performance of the age-adjusted qSOFA in predicting disease severity; three studies 24,35 evaluated the value of qSOFA in predicting ICU admission, and one study 35 evaluated the value of qSOFA in predicting the development of severe sepsis 11 . Only one study 23 was designed to evaluate the ability of the ageadjusted qSOFA to predict both ICU transfer and/or mortality within 30 days as the primary outcome.…”
mentioning
confidence: 99%
“…Patient sources were as follows: 122,943 ICU patients from four studies 13,25 , 49,448 ED patients from five studies 23,24 , and 178 pediatric tertiary referral center patients from two studies 35 . The majority of the studies were single-center studies (n = 7, 63.6%) 23,24,35 and chose cut-off criteria as ≥ 2 (n = 9, 81.8%) 13,[23][24][25]35 . Most studies (n = 9, 81.8%) 13,[23][24][25]35 adopted the 2005 IPSCC definition for age-specific vital signs criteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation